HUBUNGAN SENAM IRAMA DAN KEMAMPUAN MOTORIK KASAR ANAK USIA PRASEKOLAH DI TK KARTINI KABUPATEN GORONTALO - Akifa Syahrir; Suwarly Mobiliu; Rista Apriana; Kartin Buheli; Nur Azizah Lanjahi (Indonesian Journal of Nursing Scientific, 2025)
Rhythmic gymnastics is a fun and effective form of physical activity to stimulate gross motor development in preschool children. Well-developed gross motor skills are essential to support physical activity, movement coordination, and readiness for further learning. A preliminary study at Kartini Kindergarten, Gorontalo Regency, showed that several children experienced difficulties in performing basic movements such as jumping, maintaining balance, and following rhythmic movements properly. This study aimed to determine the relationship between participation in rhythmic gymnastics and gross motor skills among preschool children at Kartini Kindergarten, Gorontalo Regency. This study employed a quantitative descriptive and analytical design with a cross-sectional approach. The population consisted of all preschool children at Kartini Kindergarten, and total sampling was applied, resulting in 67 respondents. Data were collected using structured observation sheets and analyzed using the Spearman correlation test. The results indicated a strong and significant positive relationship between rhythmic gymnastics participation and gross motor skills (p-value = 0.000; r = 0.672). The study concludes that higher participation in rhythmic gymnastics is associated with better gross motor skills in preschool children. Rhythmic gymnastics is recommended to be implemented regularly and systematically as part of early childhood education programs to optimize children’s gross motor development.